2015
DOI: 10.1371/journal.pone.0132463
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Interplay between Thyroid Papillary Carcinoma and Hepatic Fibrosis

Abstract: BackgroundA high prevalence of thyroid papillary cancer was reported in hepatitis-C-virus (HCV) positive patients. However, the mechanistic role of hepatic-fibrosis in thyroid malignancy progressions is still unclear.AimWe aimed to study the immune-modulatory interactions between thyroid papillary carcinoma and hepatic-fibrosis.MethodsHepatic-fibrosis was induced in nude-nu-male mice by intra-peritoneal administration of carbon-tetrachloride. To induce thyroid-tumor, a thyroid papillary carcinoma cell line (NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previous studies have found that an increased level of VEGF along with VEGF-C and their receptors VEG-FR-2 and VEGFR-3 are related with LNM of PTC [36,37]. Muhanna et al [38] reported that VEGF level was significantly increased in mice with hepatic fibrosis due to liver function damage. HBV infection can lead to chronic liver injury and then cause hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found that an increased level of VEGF along with VEGF-C and their receptors VEG-FR-2 and VEGFR-3 are related with LNM of PTC [36,37]. Muhanna et al [38] reported that VEGF level was significantly increased in mice with hepatic fibrosis due to liver function damage. HBV infection can lead to chronic liver injury and then cause hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 96%
“…A study has shown that thyroid autoantibodies were observed in 83% of HCV patients with PTC and 31% of HCV patients without TC, suggesting people may suffer from an increased risk of TC after HCV infection [ 16 ]. However, HCV is an RNA virus that cannot be integrated into the host genome, and its oncogenic potential must be exerted through an indirect mechanism [ 59 ]. Therefore, we can hypothesize that autoimmune thyroid disease mediated by chronic HCV infection may lead to thyroid carcinogenesis.…”
Section: Hcv and Tcmentioning
confidence: 99%